PENINGKATAN KAPASITAS KESEHATAN PASIEN PASCA STROKE PADA KOMUNITAS STROKE DI SOLO SELATAN - Rahayu, Umi Budi (Universitas Muhammadiyah Surakarta, 2019)
The purpose of this service activity is to provide counselling, examination and education of post-stroke patients in South Solo. This activity was carried out in the South Square of the Surakarta Palace, which included blood pressure checks, pulse and counselling and education about strokes. This activity was attended by approximately 15 post-stroke patients who were members of the stroke community in South Solo. Most patients show relatively good examination results, both blood pressure, pulse and breathing. A small portion has a rather high tension. Counselling was carried out followed by a question and answer session, questions and answers were dominated by issues such as what food could be consumed if suddenly it felt heavy and weak what to do, what exercise was safe to do, how to get rid of the stiffness or by consulting specifically. Education is done by the demonstration of various activities that can be done at home, such as how to get up to sit, sit right or demonstrate the right way to walk. Keywords: Post Stroke, Examination, Counseling, Education, Stroke Community